2012
DOI: 10.1063/1.3676435
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of thermal conductivity on structural parameters in porous samples

Abstract: The in-plane thermal conductivity of porous sintered bronze plates was studied both experimentally and numerically. We developed and validated an experimental setup, where the sample was placed in vacuum and heated while its time-dependent temperature field was measured with an infrared camera. The porosity and detailed three-dimensional structure of the samples were determined by X-ray microtomography. Lattice-Boltzmann simulations of thermal conductivity in the tomographic reconstructions of the samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This model, Eq. (32), which considers the contribution of the only solid phase, provides good predictions when air is the working fluid but becomes inaccurate when the conductivity of the fluid phase is comparable to that of the solid. A similar relation was provided by Ma and Ye [71], in which the 1/3 term is replaced by a shape factor: this factor can be interpreted as the average of dimensionless temperature derivative weighted by volumes of cell walls [71].…”
Section: Empirical Correlationsmentioning
confidence: 98%
See 1 more Smart Citation
“…This model, Eq. (32), which considers the contribution of the only solid phase, provides good predictions when air is the working fluid but becomes inaccurate when the conductivity of the fluid phase is comparable to that of the solid. A similar relation was provided by Ma and Ye [71], in which the 1/3 term is replaced by a shape factor: this factor can be interpreted as the average of dimensionless temperature derivative weighted by volumes of cell walls [71].…”
Section: Empirical Correlationsmentioning
confidence: 98%
“…At the moment, a significant effort is devoted to describing the foam structure in a more realistic way: from this perspective, X-ray computed microtomography (μ-CT) appears a promising and appealing approach to be coupled to numerical simulations. The literature includes several works dealing with μ-CT, not only limited to metal foams or thermal conductivity estimations [1,3,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The literature offers a wide set of analytical and empirical correlations for the estimation of the effective thermal conductivity of metal foams.…”
Section: Introductionmentioning
confidence: 99%
“…From the microscopic viewpoint, the porous ceramic material can be simplified to a three-dimensional lattice of cubic cells and the interfacial thermal conductivity among the crystallites play a dominant role in affecting the overall thermal transport [15]. It was further experimentally confirmed that a higher interfacial thermal conductivity among the connected bronze particles would remarkably boost the thermal conductivity of sintered porous bronze materials [16]. Inspired by the abovementioned up-to-date observations, we could see a great limitation of thermal transport occurring in the materials system with inhomogeneous pore size, and thus we endeavor to reveal the underlying mechanisms for inhomogeneity in influencing the thermal transport and to design the universal porous materials with lower thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the effective thermal conductivity of porous materials is very complex because it is dependent not only on the porosity, but also on the macroscopic structure of the materials. As a matter of fact, the way the solid components are connected developing a three-dimensional shape plays an important role [14]. The effective thermal conductivity of fibrous materials is the result of three modes of heat transfer: conduction in the solid and gaseous phase, convection in the gas, and radiation [15].…”
Section: Introductionmentioning
confidence: 99%